Композиційні системи з використанням термоактивованих відходів паперового виробництва для дорожнього будівництва - Гідей, Володимир Володимирович (Національний університет «Львівська політехніка», 2023)
Дисертаційна робота присвячена вирішенню завдання отримання композиційних систем з використанням термоактивованих відходів паперового виробництва для дорожнього будівництва і встановлення особливостей формування комплексу фізико-механічних та експлуатаційних властивостей цементних дорожніх бетонів та укріплених грунтів з покращеними властивостями.The dissertation work is devoted to solving the task of obtaining composite systems using thermally activated wastepaper for road construction and establishing the formation peculiarities of a complex of physical, mechanical and operational properties of pavement concrete and stabilized soils with improved properties. In the first chapter, on the basis of a literature critical review, theoretical principles and experimental data on ways to improve the properties of pavement structure elements with the possibility of using wastepaper residues are considered. It is shown that road constructin is a material- and energy-intensive industry that consumes a significant amount of natural resources, so it is viable to seek for partial replacement of natural materials with industrial waste, which at the same time will reduce the impact on the environment.
Composite systems using thermally activated wastepaper for road construction
Keywords: термоактивовані відходи паперового виробництва, композиційні в’яжучі системи, стабілізація та укріплення грунтів, деформаційні властивості грунту, додаткові цементуючі матеріали, гідратація, портландцемент, хімічні добавки, суперпластифікатор, доменний гранульований шлак, міцність на стиск і згин, тріщиностійкість цементобетону, дорожні покриття, thermally activated paper waste, composite binding systems, stabilization and strengthening of soils, deformation properties of soil, supplementary cementitious materials, hydration, Portland cement, chemical admixtures, superplasticizer, granulated blast furnace slag, compressive and flexural strength, fracture resistance of cement concrete, road pavement